Physical Controls on Biogeochemical Processes in Intertidal Zones of Beach Aquifers. Issue 11 (15th November 2017) - Heiss, James W.; Post, Vincent E. A.; Laattoe, Tariq; Russoniello, Christopher J.; Michael, Holly A.
Abstract: Marine ecosystems are sensitive to inputs of chemicals from submarine groundwater discharge. Tidally influenced saltwater‐freshwater mixing zones in beach aquifers can host biogeochemical transformations that modify chemical loads prior to discharge. A numerical variable‐density groundwater flow and reactive transport model was used to evaluate the physical controls on reactivity for mixing‐dependent and mixing‐independent reactions in beach aquifers, represented as denitrification and sulfate reduction, respectively. A sensitivity analysis was performed across typical values of tidal amplitude, hydraulic conductivity, terrestrial freshwater flux, beach slope, dispersivity, and DOC reactivity. For the model setup and conditions tested, the simulations demonstrate that denitrification can remove up to 100% of terrestrially derived nitrate, and sulfate reduction can transform up to 8% of seawater‐derived sulfate prior to discharge. Tidally driven mixing between saltwater and freshwater promotes denitrification along the boundary of the intertidal saltwater circulation cell in pore water between 1 and 10 ppt. The denitrification zone occupies on average 49% of the mixing zone. Denitrification rates are highest on the landward side of the circulation cell and decrease along circulating flow paths. Reactivity for mixing‐dependent reactions increases with the size of the mixing zone and solute supply, while mixing‐independent reactivity is controlled primarily by solute supply. The results provide insights into the types of beaches most efficient in altering fluxes of chemicals prior to discharge and could be built upon to help engineer beaches to enhance reactivity. The findings have implications for management to protect coastal ecosystems and the estimation of chemical fluxes to the ocean. Key Points: Denitrification and sulfate reduction in beach aquifers are strongly affected by hydrology and physical characteristics of beaches Sandy beaches can attenuate 100% of land‐derived nitrate prior to discharge Mixing‐dependent reactivity increases primarily with the size of the mixing zone, mixing‐independent reactivity increases with solute supply